Kilka słów o klinikach prawa - Klauze, Magdalena (Wydawnictwo Naukowe Instytutu Filozofii, 2013)
Clinical teaching reflects the need to combine theory in the teaching of the law and practical skills. It creates the possibility of „being a lawyer” still at the stage of university education. Currently, legal clinics program was introduced at all Polish law schools – both public and private. The essence of legal clinics is to enable students to acquire the necessary skills in „safe” conditions under the guidance and supervision of the academic teachers. It should be remembered that the aspect of teaching is the primary purpose of the law clinics. This means that regardless of the social mission, the clinics give free legal assistance to poor people, it is as if only „side effect” of the educational process.
A few words about legal clinics
Keywords: legal education; legal clinic; student; supervisor; skills